Thirteenth serogroup of Legionella pneumophila isolated from patients with pneumonia. - Lindquist, D S (1988)
A Legionella-like organism (strain 82A3105; ATCC 43736) was isolated from a lung aspirate taken from a patient with pneumonia. Results of physiologic, gas-liquid chromatographic, genetic, and serologic tests showed that strain 82A3105 and four additional clinical isolates belong to a new Legionella pneumophila serogroup, serogroup 13.